Things that make white people uncomfortable - Bennett, Michael; Zirin, Dave (Haymarket Books, 2019)
Young reader's edition of the author's best-seller "Things That Make White People Uncomfortable." Examines the role and responsibility of black athletes to speak out against racial injustice and police violence. Highlights the relationship between these athletes and college and professional athletic organizations.